Letaldus of Micy, Germigny-des-Prés, and Aachen: Histories, Contexts, and the Problem of Likeness in Medieval Architecture - Shaffer, Jenny H. (Viator, 2006)
Abstract Architectural historians, focused on whether form or meaning had primacy in the medieval “copy,” have debated the significance and value of Letaldus of Micy’s statement that Theodulf’s oratory at Germigny-des-Prés was “manifestly in the likeness” of Aachen, as Germigny-des-Prés bore little formal resemblance to Charlemagne’s famous chapel. Letaldus’s quote, however, has been divorced from its textual and historical contexts. Considered as part of his tenth-century Miracula Sancti Maximini and the circumstances of its production, Letaldus’s association of the ninth-century buildings confirms Richard Krautheimer’s well-known assertion that meaning was primary in medieval notions of likeness, voicing an image of a Carolingian past remembered in light of fierce present struggles within the monastic world of the Orléanais. Indeed, rather than answering the question of whether Germigny-des-Prés was built as a “copy” of Aachen, Letaldus’s quote raises the issue of how buildings’ complex, layered, and transforming meanings are rooted in time and place.